Workplace violence in healthcare settings: The risk factors, implications and collaborative preventive measures - Mei Ching Lim; Mohammad Saffree Jeffree; Saihpudin Sahipudin Saupin; Nelbon Giloi; Khamisah Awang Lukman (Elsevier Ltd, 2022)
Violence at work refers to acts or threats of violence directed against employees, either inside or outside the workplace, from verbal abuse, bullying, harassment, and physical assaults to homicide. Even though workplace violence has become a worrying trend worldwide, the true magnitude of the problem is uncertain, owing to limited surveillance and lack of awareness of the issue. As a result, if workplace violence, particularly in healthcare settings, is not adequately addressed, it will become a global phenomenon, undermining the peace and stability among the active communities while also posing a risk to the population’s health and well-being. Hence, this review intends to identify the risk factors and the implications of workplace violence in healthcare settings and highlight the collaborative efforts needed in sustaining control and prevention measures against workplace violence.